A catalog of 159, 238 white dwarf ages. Issue Volume 15:Issue S357(2019) (October 2019) - von Hippel, Ted; Moss, Adam; Kloc, Isabelle; Moticska, Natalie; Sargent, Jimmy; Robinson, Elliot; Stenning, David; van Dyk, David; Jeffery, Elizabeth; Fouesneau, Morgan; Bailer-Jones, Coryn
Abstract: We employ Pan-STARRS photometry, Gaia trigonometric parallaxes, modern stellar evolution and atmosphere models, and our Bayesian fitting approach to determine cooling and total ages for 159, 238 white dwarfs. In many cases we are able to derive precise ages (better than 5%) for individual white dwarfs. These results are meant for broad use within the white dwarf and stellar astrophysics communities and we plan to make available on-line the posterior distributions for cooling age, total age, initial stellar mass, and other parameters.